Cilostazol-inhibited RhoA/NF-κB signaling mitigates hippocampal inflammation and post-stroke depression - Zhang, Yuling; Li, Yichen; Wu, Yafang; Tan, Xiying; Ji, Tingting; Tang, Chaozhi (Frontiers in Pharmacology, 2025)
IntroductionAlthough approximately one-third of stroke survivors develop post-stroke depression (PSD), clinically recommended preventive treatments currently are unavailable. Cilostazol, an established stroke therapeutic, has demonstrated potential in preventing PSD, however, its neuroprotective mechanisms remain unclarified. This study elucidates the molecular pathways via which cilostazol may protect against PSD development.MethodsMiddle cerebral artery occlusion (MCAO) was performed on C57BL/6J mice to establish an ischemic stroke (IS) model. Subsequently, the IS mice were treated with cilostazol and subjected to chronic unpredictable mild stress (CUMS) to induce PSD. Cilostazol’s PSD prevention efficacy was evaluated using the sucrose preference, open field, tail suspension, and Morris water maze. Nissl staining and immunofluorescence labeling were used to detect cilostazol’s effects on hippocampal neuronal apoptosis and microglial activation. Western blot and quantitative polymerase chain reaction were used to investigate cilostazol’s regulation of hippocampal inflammation and apoptosis factors. Cilostazol’s potential PSD-preventive mechanism was further explored by examining the primary hippocampal neuronal apoptosis induced by RhoA-activated BV2 microglia.ResultsCilostazol intervention significantly suppressed hippocampal microglial proliferation and activation and decreased pro-inflammatory cytokine expression. These changes were associated with attenuated hippocampal neuronal swelling and apoptosis and were accompanied by apparent alleviation of depressive behaviors in CUMS-subjected IS mice. Mechanistically, in vitro experiments demonstrated that cilostazol inhibited RhoA/NF-κB signaling pathway activation in BV2 microglia, leading to decreased tumor necrosis factor-alpha and interleukin-1β secretion. The neuroprotective effects of cilostazol, potentially mediated via a cAMP-dependent reduction of microglia-induced neuronal damage, may contribute to the improvement of depressive-like behaviors in mice with PSD.ConclusionCilostazol may alleviate hippocampal inflammation by inhibiting RhoA/NF-κB signaling pathway activation in the microglia, providing neuronal protection and PSD prevention effects.